Mechanical properties and damage mechanism of steel fiber reinforced cemented tailings backfill - Yanbi XIONG; Xiaohui LIU; Haiyong CHENG; Shunchuan WU; Jing ZHANG; Weihua LIU; Rujun TUO; Zemin LIU (工程科学学报)
To explore the influence of steel fibers (SFs) on the mechanical properties and damage/failure mechanisms of backfill, fiber-reinforced cemented tailings backfill (FR–CTB) is taken as the research subject to investigate the impact of SF content on the backfill mechanical properties. Digital image correlation (DIC) technology is employed to monitor the full-field strain of specimens and track crack development. Additionally, the microscopic strengthening mechanism of SF on backfill is studied. The results indicate that with increasing SF content and curing age, the uniaxial compressive strength, splitting tensile strength, and shear strength of FR–CTB increase to varying extents. The optimal strengthening effect occurs at an SF content of 20 kg·m−3, but this effect diminishes notably when SF content exceeds 20 kg·m−3. The presence of SFs significantly restrains crack expansion in the backfill, reduces stress concentration at crack tips, effectively prevents crack propagation, and improves overall specimen deformation. Compared with nonfiber-reinforced backfill, steel fiber-reinforced backfill exhibits characteristics of resisting microcracks without fracturing. DIC damage evolution images captured at various loading stages illustrate the initiation, propagation, and penetration of cracks in backfill specimens during different failure processes. Furthermore, from a microstructural perspective, the addition of SFs results in a more complete and denser structure where tailings particles, fibers, and hydration products such as hydrated calcium silicate (C–S–H) gel, flocculent ettringite (Aft), and large calcium hydroxide (CH) crystals interact. During loading, the strengthening effect of SFs is mainly manifested through bridging and pull-out mechanisms within the tail-cement matrix. The presence of hydration products increases the roughness of the SF surface, thereby enhancing friction between SF and the cement-tailings matrix. This improves the ability to absorb external loads and enhances the mechanical properties of FR–CTB. As the SF content increases, more fibers absorb fracture energy by effectively pulling out when specimens crack. Optimal mechanical properties of FR–CTB are achieved at an SF content of 20 kg·m−3. However, exceeding this threshold (25 kg·m−3) negatively impacts the cement matrix structure, increasing porosity and consequently decreasing the mechanical properties of the backfill. Finally, SPSS curve estimation is employed to establish a strength calculation model for backfill at various ages. This model exhibits high accuracy in predicting the strength of steel fiber-reinforced backfill.